State Plan Proposals 1963-64 Government of West Bengal - Planning Commission (Planning Commission, 1963)
The outlays for 1963-64 in West Bengal's Third Five Year Plan - have been determined generally on the basis of the directives approved in the national Defence Council's emergency meeting held on November 4th end 5th, 196r. While the total financial provision of Rs. 293 crores for the Third Five Year Flan remains unaltered, there has been considerable shifting of emphasis in accordance with the new priorities which have emerged in the context of the National emergency
Government of West Bengal Development Department
Government of West Bengal Development Department
Keywords: State Plan for West Bengal; Past performance; Resources; Outlay for 1963-64; Summary Statement of State Plan Outlay; Calcutta Metropolitan Planning Organisation; Proposals for Advance Action for the Fourth Plan; State Plan Proposals; Forests; Financial Provision